Special education transition services for students with disabilities - Bakken, Jeffrey P.; Obiakor, Festus E. (Emerald Publishing Limited, 2019)
While services for students with disabilities have been vastly improved in recent years, and research has created far greater awareness for the issues they face, there are still many obstacles to overcome as these students progress through the education system. This book discusses the considerable challenges these students conquer in education, varying relationships with teachers and academics, learning resources, and everyday social situations. Beginning with an introduction to transition services and students with disabilities, this invaluable text goes on to discuss a wide range of disability topics. Leaders in the field of transition services present recent research on students with learning disabilities, deaf/hard of hearing students, those who have visual impairments, autistic students, those with extensive support needs, physical disabilities, and more. This book is an excellent resource for special education researchers, scholars, practitioners, and professionals who teach and serve students with disabilities.
Chapter 1. Special education transition services for students with disabilities: an introduction / Jeffrey P. Bakken Chapter -- 2. Transition services for students with learning disabilities / Margaret P. Weiss and Michael Faggella-Luby -- Chapter 3. Memories of warmth: transition for students with emotional and/or behavioral disorders / Frederick J. Brigham, John William McKenna, and Michele M. Brigham -- Chapter 4. Special education transition services for students with intellectual disabilities / Emily Bouck and Jiyoon Park -- Chapter 5. Special education transition services for students who are deaf/hard of hearing / Christy Borders, Marcus Daczewitz, and Kristi Probst -- Chapter 6. Special education transition services for students with visual impairments / Stacy Kelly -- Chapter 7. Special education transition services for students with autism / Shannon Stuart and James C. Collins -- Chapter 8. Special education transition services for students with extensive support needs / Sarah, R. Carlson, Vidya D. Munandar, Michael Wehmeyer, and James R. Thompson -- Chapter 9. Special education transition services for students with traumatic brain injuries / Sunday Obi, Festus E. Obiakor, and Stephanie L. Obi -- Chapter 10. Speech-language pathologists' role in promoting student participation in interprofessional transition planning teams / Ginger Collins and Julie A. Wolter -- Chapter 11. Transitioning students with physical disabilities and other health impairments / Eugene F. Asola and Samuel R. Hodge -- Chapter 12. Foundational assumptions for successful transition: examining alternatively certified special educator perceptions / John William McKenna, Frederick J. Brigham, Melissa Parenti, and Brittany Hott -- Chapter 13. Special education transition services for students with disabilities: moving forward / Kagendo Mutua, Amy Williamson, Catherine Price, and Dongjin Kwon -- Index.
Includes index.
Print version record.
Keywords: Youth with disabilities -- Education; School-to-work transition; Students with disabilities -- Services for; Social Science, People with Disabilities; Teaching of students with specific learning difficulties, needs